Biosorption of lead, copper, cadmium, and mercury by brown seaweeds (Sargassum sp. and Turbinaria ornata) - Ingeniero, Riel Carlo; Boren, Michaela; Tan, Emee; Perez, Teresita (2011)
Biosorption is a process that uses inexpensive biomass to sequester toxic heavy metals and is particularly useful for the removal of trace levels of contaminants for industrial effluents. Several types of biomass have been tested for heavy metal sorption capacity which includes bacteria, fungi, algae, and aquatic macrophytes. Marine macroalgae are one of the organisms proven to have high heavy metal adsorption capacity due to the functional groups such as carboxyl groups from amino acids and polysaccharides and sulfhydral groups present in the biomass of seaweeds. In this study, dried biomass of T. ornata and Sargassum sp. were tested for its heavy metal adsorption capacity. The maximum adsorption capacity of Sargassum sp. and T. ornata (qmax range = 84.09-129.87) exceeded many previously reported uptakes by other type of biomass such as that of granulated activated carbon (qmax = 5.08mh/g) and Chlorella vulgaris (qmax = 58.8mg/g), T. ornata absorbed higher amounts of cadmium and mercury. Results of the experiments also showed that pH and contact time affected the adsorption of heavy metals from aqueous solutions. Based on the FTIR analysis conducted, the carboxyl and hydroxyl groups were the functional groups responsible for sorption of the heavy metals. Sargassum and Turbinaria were proven to be effective metal biosorbents.
Keywords: Lead; Cadmium; Mercury contamination; Heavy metals; Marine algae